Nursing Entrepreneurship Opportunities Through Sartika Products (Innovative Injection Sards) To Prevent Hospitalization In Children By Using Flannel Fabric Waste - Dewi, Prischa Amelliana; Puspita, Asih Purwandari Wahyoe; Zahra, Mutiara Alya; Sari, Dina P; Putri, Dinda Adiningsih; Rahmawati, Astri (Universitas Pendidikan Indonesia, 2023)
Pediatric hospitalization is a medical experience that is often necessary, but can have a significant impact on children. In these situations, children are exposed to unfamiliar environments and medical procedures that may be frightening, including the use of needles. In addition, traumatic or painful experiences with needles during hospitalization can trigger the development of needle phobia in children. These phobias can impact their physical and mental well-being, interfere with medical care, and increase anxiety. innovative health product innovation injectable gloves (sartika) to prevent hospitalization in children by using flannel waste as a nursing entrepreneurship opportunity aimed at (1) overcoming the impact of hospitalization on sick children in hospitals/health centers/clinics, (2) as a medium for distraction/trauma healing so that children do not experience trauma after medical procedures (injections) because Sartika uses animated characters that are liked by children, (3) creates cheap, creative and innovative health products, (4) as one of the steps to preserve the environment through the use of 3R flannel waste (Reduce, Reuse and Recycle). Forms of entrepreneurial activity include the preparation, implementation, packaging and evaluation stages of Sartika products. Target The target users of Sartika's innovative products are pediatric patients in hospitals, health centers or clinics. The results of the activity show that the use of Sartika products has a positive impact on supporting the performance of medical staff (nurses) in hospitals during medical procedures (injections), child patients become more cooperative and children are distracted because Sartika products use animated characters that are liked by children, so that children do not experience trauma after medical procedures (injections). Community education based on a family approach is considered effective in overcoming the impact of hospitalization and trauma/phobia towards injection needles.